2013
DOI: 10.3748/wjg.v19.i37.6165
|View full text |Cite
|
Sign up to set email alerts
|

HER2 therapies and gastric cancer: A step forward

Abstract: Gastric cancer usually is diagnosed in advanced stages and thus current medical practice affords limited therapeutic options. However, recent studies established the role of human epidermal growth factor receptor 2 (HER2) in clinical management. Trastuzumab, an anti-HER2 monoclonal antibody, acquired a main role in advanced gastric cancer harboring HER2 overexpression and/or amplification improving survival to 17.1 mo according to trastuzumab for gastric cancer phase III trial results. Also, new promising drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 42 publications
0
29
0
1
Order By: Relevance
“…The ToGA (trastuzumab for gastric cancer) randomized trial demonstrated a higher response rate (13-8 months) in a group of advanced gastric cancer patients with HER2--positive that received trastuzumab in combination with chemotherapy vs. chemotherapy alone (11-1 months). Other studies confirm that the combination of trastuzumab or pertuzumab with standard chemotherapy prolongs PFS and OS in HER2-positive patients [36][37][38][39].…”
Section: The Significance Of Fish Analysis In Qualification For Anti-mentioning
confidence: 74%
See 1 more Smart Citation
“…The ToGA (trastuzumab for gastric cancer) randomized trial demonstrated a higher response rate (13-8 months) in a group of advanced gastric cancer patients with HER2--positive that received trastuzumab in combination with chemotherapy vs. chemotherapy alone (11-1 months). Other studies confirm that the combination of trastuzumab or pertuzumab with standard chemotherapy prolongs PFS and OS in HER2-positive patients [36][37][38][39].…”
Section: The Significance Of Fish Analysis In Qualification For Anti-mentioning
confidence: 74%
“…Moreover, it has been reported that dacomitinib -pan-HER inhibitor can be used in the effective treatment of gastric cancer. Till now, it has not been strictly defined which method of HER2 disorder determination should be carried out in the correct qualification of patients for trastuzumab therapy [34,[36][37][38][39].…”
Section: The Significance Of Fish Analysis In Qualification For Anti-mentioning
confidence: 99%
“…Trastuzumab, a human epidermal growth factor receptor type 2 (HER2) monoclonal antibody, was the first such agent receiving Food and Drug Administration (FDA) and European Medicine Agency (EMA) approval because it was shown to improve overall response rate (ORR), progression free survival (PFS), and overall survival (OS) when added to cisplatin-based chemotherapy in patients with HER2 over-expressing GC [12][13][14][15]. However, HER2 over-expressing tumors represent approximately 20% of the total numbers of GC cases, and the need for additional targeted agents is urgent [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…İlerlemiş ve metastatik mide ve gastroözofageal bileşke kanserlerinde kombine kemoterapi ve trastuzumab tedavisiyle, tek başına kemoterapiye göre sağkalım avantajının gösterilmesi, trastuzumabı mide kanserlerinde de tedavi seçeneği haline getirmiştir (7). Bu gelişmeyle birlikte günlük pratikte tüm yeni tanı alan mide kanserlerinde de HER2 İHK testi yapılması önerilir hale gelmiştir (26).…”
unclassified